Behavioral experience induces zif268 expression in mature granule cells but suppresses its expression in immature granule cells - Huckleberry, Kylie A.; Kane, Gary A.; Mathis, Rita J.; Cook, Sarah G.; Clutton, Jonathan E.; Drew, Michael R. (Frontiers in Systems Neuroscience, 2015)
Thousands of neurons are born each day in the dentate gyrus (DG), but many of these cells die before reaching maturity. Both death and survival of adult-born neurons are regulated by neuronal activity in the DG. The immediate-early gene (IEG) zif268 appears to be an important mediator of these effects, as its expression can be induced by neural activity and knockout of zif268 impairs survival of adult-born neurons (Richardson et al., 1992; Veyrac et al., 2013). Despite the apparent importance of zif268 for adult neurogenesis, its behavior-induced expression has not been fully characterized in adult-born neurons. Here we characterize behavior-evoked expression of zif268 in mature and newborn dentate granule cells (DGCs). We first quantified zif268 expression in doublecortin-positive (DCX+) immature neurons and in the general granule cell population after brief exposure to a novel environment (NE). In the general granule cell population, zif268 expression peaked 1 h after NE exposure and returned to baseline by 8 h post-exposure. However, in the DCX+ cells, zif268 expression was suppressed relative to home cage for at least 8 h post-exposure. We next asked whether suppression of zif268 in DCX+ immature cells occurs in other behavioral paradigms that recruit the hippocampus. Exposure to Morris water maze (MWM) training, an enriched environment, or a NE caused approximately equal suppression of zif268 expression in DCX+ cells and approximately equal activation of zif268 expression among the general granule cell population. The same behavioral procedures activated zif268 expression in 6-week-old BrdU-labeled adult-born neurons, indicating that zif268 suppression is specific to immature neurons. Finally, we asked whether zif268 suppression varied as a function of age within the DCX+ population, which ranges in age from 0 to approximately 4 weeks. NE exposure had no significant effect on zif268 expression in 2- or 4-week-old BrdU-labeled neurons, but it significantly suppressed zif268 expression in 3-week-old neurons. In summary, behavioral experience transiently activated expression of zif268 in mature granule cells but caused a more long-lasting suppression of zif268 expression in immature, adult-born granule cells. We hypothesize that zif268 suppression inhibits memory-related synaptic plasticity in immature neurons or mediates learning-induced apoptosis of immature adult-born neurons.